Determinación del impacto ambiental y propuesta de mitigación para el proyecto: Ampliación, mejoramiento e instalación del sistema de agua potable y del sistema de saneamiento básico en las localidades de pueblo libre y nuevo Huancabamba - Mori López, Manuel (2015)
The project is located in the Free People and New Huancabamba towns, Moyobamba district, Moyobamba province, San Martín department and has as its central goal improve the public. health service, by providing a basic . infrastructure for drinking water and sanitation, which shall be governed on the basis of the technical standards of sanitation at the nationallevel, as a basis for improvement of their quality life and as a sample of the participation of the State as prometer of development, investment that demand the project amounts to SI. 11 108 363.74 ·.,.. The general objective of the study · is · to identify the potential environmentaL · .,,. impacts, to develop the management tools and raise the costs claiming override, mitigate and/or minimize negative environmental impacts and strengthen the direct and indirect positive impacts to occur during the execution of the work and operation of the project based on its proper identification and taking into account the activities to be carried out to comply with the specifications that the project requires. The study at its first part presents the description of the project, described the existing infrastructure and the new, the Environmental Diagnosis includes physical and biological aspects, with weather information, identification of the areas of lite and their characteristics, geology, geomorphology, soils, coverage and current use of the land, hydrology, vegetation, crops, animals, wildlife and conservation areas clase to the work area. The analysis of the influence area of the project impacts has been considered a direct area of influence that covers 25 meters on each side of the lines of driving and adduction, as well as the entire territory covering the scope of the localities of Free People and New Huancabamba. For the identification of environmental impacts occur in the execution of the project, produced a cause-effect qualitative matrix that considers the actions of the project by stages compared to the environmental parameters to be affected by the activity, evaluation is a product of the contribution of the work of the team of professionals who participated in the study. The impacts identified in the implementation stage were: air pollution by emission of particulate material and combustion gases, deterioration of the podiatric characteristics or geomechanics of the soil, soil loss by change or disappearance of the plant cover and contamination of water by increasing concentration of sediments, dissolved and suspended solids in the water, noise pollution a':ld generation of employment, these imp~cts both at the stage of implementation, operation and maintenance. Presents the Environmental Management Plan that includes preventive measures that should be implemented in order to mitigate the negative impacts, basically arises measures to counteract the emission of gases and particulate material, generating noise, affectation to the flora and fauna, the breathability local, etc. There is also the program of citizen participation, program of solid waste management, program of monitoring and control, which includes monitoring of the main parameters of quality of surface water and body receiver. Similarly the co~tingency plan to deal with natural events as well as accidents. ·And·:fi.naYiy the bread ot closure as final. adivlty. both tor the final stage of the construction phase and the end of the useful lite of the project. Key words: useful lite, drinking water.